Kuwait : From Reconstruction to Accumulation for Future Generations - Wilson, John.; Chalk, Nigel; El-Erian, Mohamed; Fennell, Susan (Washington, D.C. : International Monetary Fund, 1997)
Kuwait has made an impressive recovery from the damage and disruptions caused by the Iraqi invasion in 1990, as evidenced by the restoration of basic economic and social services, the recovery of the oil sector, the rehabilitation of infrastructure, and the steady reduction in the fiscal and balance of payments deficits. This paper examines recent developments in the Kuwaiti economy and discusses the country's medium-term policy challenges of saving for future generations, strengthening the financial sector, and improving the functioning of the labor market.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet